Clearing Crime in Prime-Time: The Disjuncture Between Fiction and Reality - Rhineberger-Dunn, Gayle (American journal of criminal justice, 2016)
Crime dramas provide entertainment to millions of Americans. The impact of viewing these programs on perceptions and expectations of police is a concern for practitioners, researchers and policy makers. While a growing body of research is identifying factors associated with the probability of clearance in offenses reported to police, a dearth of research looks at the portrayal of police efficiency in apprehending offenders in popular crime dramas. This study examines the depictions of police investigations across four fictional crime dramas. The authors find offenses are cleared at much higher rates than national averages and that several case characteristics typically associated with clearance in actual cases do not share the same relationship in these fictional programs. Results indicate substantial variation between programs in the depiction of the collection and utility of DNA evidence in assisting investigators to identify suspects. Findings are discussed in relation to data collected from actual police departments.